One Last Breath - Jackson, Lisa & Bush, Nancy 1953; McKay, Julie (Narrator) (Grand Haven, MI : Brilliance Audio, 2018)
Rory Abernathys wedding to Liam Bastian turned into a bloodbath. She fled after stabbing a masked intruder, just before a gunman opened fire on the wedding party. Five years on, Rory still has no idea who was behind the attacks. Fearful she and her daughter remain targets, shes made a new life far from Liam and the wealthy, powerful Bastians. But even in remote Point Roberts, Washington, she cant hide from the past.
Keywords: Murderers -- Fiction; Runaway wives -- Fiction; Washington (State) -- Fiction